Analysis of tolvaptan non‐responders and outcomes of tolvaptan treatment of ascites. Issue 7 (18th November 2018) - Iwamoto, Takuya; Maeda, Masaki; Saeki, Issei; Hidaka, Isao; Tajima, Kunihiko; Ishikawa, Tsuyoshi; Takami, Taro; Sakaida, Isao
Abstract: Background and Aim: The goals of the study were to identify an effective treatment for ascites and to examine the influence of tolvaptan on outcomes by investigating non‐responders to tolvaptan and comparing outcomes of hepatic cirrhosis in patients treated with and without tolvaptan. Methods: In Study 1, of 145 patients with hepatic cirrhosis who were treated with tolvaptan between September 2013 and March 2018, 45 who did not achieve weight loss of ≥1.5 kg within one week were investigated. In Study 2, 83 patients who received tolvaptan for ascites between September 2013 and March 2017 were compared with 131 patients who were treated for ascites without use of tolvaptan between January 2006 and January 2012. Results: In Study 1, the 45 patients were divided into three groups based on changes in dosing of diuretics. Renal function was retained in the dose reduction group compared with that in the other groups, and the rate of discharge with remission and the outcomes were also favorable in patients with dose reduction. In Study 2, survival was significantly more favorable in patients treated with tolvaptan. Conclusions: Dose reduction of diuretics may be effective for patients with reduced renal function for whom tolvaptan is ineffective or the effect is insufficient and may also improve outcomes of patients with hepatic cirrhosis by preventing a decline in renal function caused by an increased dose of diuretics.